Perceptions and Attitudes of Indonesian Generation Z towards Debt - Penitaliasih Dwi Astuti; Taufik Faturohman (UNIVED Press, 2024)
This research aims to understand the relationship between the demographic profile of Generation Z in Indonesia and their perceptions and behavior towards debt. Data collection was carried out through an online survey of 400 respondents in the period July to September 2023. Analysis of the data that had been collected was carried out using descriptive statistics, and continued using the Kruksal Wallis and Mann Whitney U Test to see more deeply whether there were statistically significant differences. between two or more independent variables. The results of this study found that there were significant differences in the influence of gender and income on their perceptions and behavior toward debt. Apart from that, there is no significant difference between level of education and employment and perceptions and behavior towards debt.